Romanian milk sector in international context - Rodica Chetroiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The paper performs an analysis of the Romanian sector of milk, identifying the status at global level, under various aspects, as part of the worldwide production of milk, with reference to the place our country in the world ranking of cow milk, milk productions, cow farm sizes, milk prices in international context etc. The study also integrates the presentation of some statistical indicators describing the dynamics and variability of cow's herds and milk productions, such as average, standard deviation and coefficient of variability. Our country owns 0.43% of total cows and buffaloes worldwide and 0.6% of milk production, and at the European Union level it provides 5.04% of the flocks and 2.5-2.6% of the cow's and buffalo milk production.
Keywords: O13; Q12; Q17; 330; milk; production; global; farms